A new approach of preheating and powder sintering in electron beam powder bed fusion - Böhm, Jonas; Breuning, Christoph; Markl, Matthias; Körner, Carolin (International Journal of Advanced Manufacturing Technology, 2024)
Preheating is an essential process step in electron beam powder bed fusion. It has the purpose of establishing a sintered powder bed and maintaining an elevated temperature. The sintered powder bed reduces the risk of smoke and in combination with the elevated temperature improves the processability. Today, the line-ordering preheating scheme is widely used. This scheme does not take the previously built layers into account and results in an inhomogeneous elevated temperature and consequently in a variety of sinter degrees, which is disadvantageous for the process. The main challenge is now to modify this scheme to establish a homogeneous temperature distribution. This study addresses this challenge and analyses as well as optimises this scheme. A GPU-parallelised thermal model reveals a heterogeneous temperature distribution during preheating because of varying thermal conditions within a build job. In addition, a work-of-sintering model predicts that the sinter degree of the current powder layer on top of previously consolidated material is smaller than on top of the surrounding powder bed. This work aims to invert this trend to improve powder re-usage and material consolidation. Consequently, this work proposes an extension of the current scheme, compensating for the specific energy loss with local adjustments to the energy input. This adaption results in a uniform temperature distribution and advantageous sintering. Applying the proposed numerical model proves to be an effective method to analyse the evolving process conditions and tailor the local energy input, thereby improving the efficiency of the preheating step.<br